Analisis Kepuasan Penggunaan Media Digital dalam Penilaian Kinerja ASN Pemerintah Kabupaten Banyuwangi - Ardhi Kurniawan; Rendra Eko Wismanu; Achmad Reza Rizky; Muhammad Iqbal Humam (Jurnal Komunikasi Nusantara, 2026)
The implementation of e-government in Indonesia serves as a crucial strategy for local governments to enhance the quality, efficiency, and transparency of public services. This study aims to evaluate employee satisfaction regarding the implementation of the E-Kinerja system and the Employee Performance Monitoring System (SIM-K) in Banyuwangi Regency using the E-Government Satisfaction (EGOVSAT) framework. The methodology employed is descriptive with a quantitative approach, involving 267 respondents selected through Proportional Stratified Random Sampling from a total population of 2,561 civil servants. Measurement was conducted based on five key dimensions: utility, reliability, efficiency, flexibility/customization, and risk. The results indicate that the overall user satisfaction score reached 3.710, with a Converted Interval Value (NIK) of 92.74, categorized as "Very Good" (Service Quality A). Comparatively, the E-Kinerja application (3.730) was rated higher than SIM-K (3.689). The efficiency dimension obtained the highest score (93.36), while the risk dimension received the lowest score (89.99) due to issues with application stability. Specific findings identified weaknesses in the availability of feedback mechanisms and the completeness of features within the performance input modules. Key recommendations include the development of smartphone-based applications, improving system stability to minimize technical errors, and strengthening routine monitoring mechanisms to maintain civil servant discipline. Abstrak Implementasi e-government di Indonesia merupakan strategi krusial bagi pemerintah daerah untuk meningkatkan kualitas, efisiensi, dan transparansi pelayanan publik. Penelitian ini bertujuan untuk mengevaluasi tingkat kepuasan pegawai terhadap pelaksanaan sistem E-Kinerja dan Sistem Monitoring Kinerja Pegawai (SIM-K) di Kabupaten Banyuwangi menggunakan kerangka kerja E-Government Satisfaction (EGOVSAT). Metodologi yang digunakan adalah deskriptif dengan pendekatan kuantitatif, melibatkan 267 responden yang dipilih melalui teknik Proportional Stratified Random Sampling dari total populasi 2.561 ASN. Pengukuran dilakukan berdasarkan lima dimensi utama: utilitas, reliabilitas, efisiensi, fleksibilitas/kustomisasi, dan risiko. Hasil penelitian menunjukkan bahwa nilai kepuasan pengguna secara keseluruhan mencapai 3,710 dengan Nilai Interval Konversi (NIK) sebesar 92,74, yang dikategorikan sebagai "Sangat Baik" (Mutu Layanan A). Secara komparatif, aplikasi E-Kinerja (3,730) dinilai lebih baik daripada SIM-K (3,689). Dimensi efisiensi memperoleh skor tertinggi (93,36), sedangkan dimensi risiko mendapatkan skor terendah (89,99) karena kendala kestabilan aplikasi. Temuan spesifik mengidentifikasi kelemahan pada aspek ketersediaan sarana umpan balik dan kelengkapan fitur pada modul input kinerja. Rekomendasi utama mencakup pengembangan aplikasi berbasis smartphone, peningkatan stabilitas sistem guna meminimalisir error, serta penguatan mekanisme monitoring rutin bagi kedisiplinan ASN.